Unusual Presentation of Hydatid Cyst: Diagnosis with Bronchoscopy - ÇAKIR, ERKAN; ÇAKIR, ERKAN; OZAYDIN, E; TASCI, E; BARAN, R (My University, 2010)
Hydatid disease is one of the major health problems in countries where hydatidosis is endemic. Atypical radiological findings may lead to misdiagnosis or delay in diagnosis in these patients. A 13-year-old boy was presented who admitted to the hospital with a history of cough and hemoptysis for six months. He had a non-resolving pneumonia. Bronchoscopy showed endobronchial lesion and the diagnosis of hydatid disease was confirmed by pathological examination.